(untitled) (International Journal of Food and Nutritional Sciences, 2022)
More than 10% of cancer patients also have depression, which is a common comorbidity. A cancer diagnosis is a major life-changing event that causes a lot of mental and emotional stress. Non-pathological melancholy may be a common reaction to a cancer diagnosis, but stress that exceeds the capacity of the patient’s coping systems may lead to severe depressive disorder. Along with the apparent psychosocial components of depression, the current study also examines its biological causes, such as tissue damage, inflammatory mediators, and the chronic stress response, as well as how these immunological and endocrine pathways may contribute to depression in cancer. The investigation of potential iatrogenic depression in cancer patients continues. In order to improve quality of life and decrease mortality, depression in cancer patients must be recognised and treated. We quickly describe the most used clinical and anticipated biochemical screening methods for depression in cancer. Although there is a dearth of research on the most effective care of depression in cancer, the best mix of medicines is unknown. Interventions employed will differ for each patient but may include psychosocial therapies or medication. Given the frequent side effects of chemotherapy (such as nausea) and the need to prevent significant interactions, such as decreasing the efficacy of chemotherapeutic medications, great consideration should be given to antidepressant choice. The potential connection between the chronic stress response, which may put patients at risk for depression, and the likelihood of dying from cancer is also investigated. Future research could lead to the creation of quicker and more effective treatments for depression in cancer due to the complex interactions between the endocrine, neurological, and immune systems that are still being fully understood.